2019
DOI: 10.1080/14786419.2019.1696794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of madecassoside and catalpol in amelioration of insulin sensitivity in pancreatic (INS-1E) β-cell line

Abstract: Currently, type 2 diabetes mellitus (T2D) has emerged as global burden disease. Herbal drugs with antidiabetic activities are attracting the attention. Madecassoside and catalpol are herbal compounds having strong antioxidant and glucose lowering activity.Madecassoside and catalpol were investigated for their effect on insulin sensitivity using pancreatic INS-1E cells. Cytotoxicity of these compounds were evaluated by MTT assay. Glucose-stimulated insulin secretion (GSIS) and expression of insulin signalling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…128 Madecassoside improves insulin sensitivity in pancreatic cells to promote glucose-stimulated insulin secretion (GSIS) and to enhance expression of insulin signalling proteins without any cytotoxic effects, making it a favourable drug compound in targeting type 2 diabetes mellitus. 129…”
Section: Miscell Aneous Ac Tivitie Smentioning
confidence: 99%
See 1 more Smart Citation
“…128 Madecassoside improves insulin sensitivity in pancreatic cells to promote glucose-stimulated insulin secretion (GSIS) and to enhance expression of insulin signalling proteins without any cytotoxic effects, making it a favourable drug compound in targeting type 2 diabetes mellitus. 129…”
Section: Miscell Aneous Ac Tivitie Smentioning
confidence: 99%
“…Asiaticoside is proved to protect against mild acute pancreatitis (MAP) in caerulein‐induced MAP models by inhibiting pancreatic acinar cells necrosis, ameliorating pancreatitis‐associated histopathological changes, and lowering the severity of pancreatic tissue injury as well as pancreatitis‐associated lung injury in a severe acute pancreatitis model 128 . Madecassoside improves insulin sensitivity in pancreatic cells to promote glucose‐stimulated insulin secretion (GSIS) and to enhance expression of insulin signalling proteins without any cytotoxic effects, making it a favourable drug compound in targeting type 2 diabetes mellitus 129 …”
Section: Miscellaneous Activitiesmentioning
confidence: 99%
“…On the contrary, catalpol (30 mM) significantly increased the p-IRS, PI3K, p-AKT, and AKT proteins in HG-treated INS-1E cells. Thus, catalpol could ameliorate insulin sensitivity through the insulin-signaling pathway in β-cells [ 63 , 64 ]. Moreover, catalpol may act against T2DM-induced oxidative damage in pancreatic islet cells of HFD/STZ rats through antioxidant effects.…”
Section: Effects Of Catalpol In Diabetes Mellitusmentioning
confidence: 99%
“…Previous studies have confirmed that MA can be widely distributed to several internal organs, and reach a maximum level within 5–15 min after oral administration, however, the bioavailability of oral intake of MA is poor (less than 1%) ( 11 , 12 ). Although many beneficial effects associated with MA, such as it can promote wound healing ( 13 ), ameliorate lung fibrosis in mice ( 14 ), inhibit proliferation and invasion of liver cancer cells ( 15 ), prevent neurodegenerative diseases ( 16 ), stimulate insulin secretion ( 17 ), and relieve osteoarthritis ( 18 ) have been reported, research on the effects of MA on obesity has not yet been developed, and so this study aimed to evaluate the interplay between obesity and MA and the possible underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%